Walerian Borowczyk - Short Films and Animation - Borowczyk, Walerian (Walerian Borowczyk, 2014)
For the first decade of his career, Walerian Borowczyk exclusively made short films, initially in his native Poland, but then mostly in France, where he settled permanently in the late 1950s. This disc includes the vast majority of the shorts that he made between 1959 and 1984, apart from ones that were originally intended to accompany specific features. [www.moviemail.com]